Translation of microwave methodology to continuous flow for the efficient synthesis of diaryl ethers via a base-mediated SNAr reaction - Wiles, Charlotte; Watts, Paul (Beilstein Journal of Organic Chemistry, 2011)
Whilst microwave heating has been widely demonstrated as a synthetically useful tool for rapid reaction screening, a microwave-absorbing solvent is often required in order to achieve efficient reactant heating. In comparison, microreactors can be readily heated and pressurised in order to “super-heat” the reaction mixture, meaning that microwave-transparent solvents can also be employed. To demonstrate the advantages associated with microreaction technology a series of SNAr reactions were performed under continuous flow by following previously developed microwave protocols as a starting point for the investigation. By this approach, an automated microreaction platform (Labtrix® S1) was employed for the continuous flow synthesis of diaryl ethers at 195 °C and 25 bar, affording a reduction in reaction time from tens of minutes to 60 s when compared with a stopped-flow microwave reactor.
Keywords: automated synthesis; continuous flow; microreactor; microwave; nucleophilic substitution; organic bases

(untitled) - Frlan, R.; Kikelj, D. (Synthesis, 2006)

(untitled) - Boger, D. L.; Yohannes, D. (J. Org. Chem., 1989)

(untitled) - Gottsegen, Á.; Nógrádi, M.; Vermes, B.; Kajtár-peredy, M.; Bihátsi-karsai, É. (Tetrahedron Lett., 1988)

(untitled) - Cirla, A.; Mann, J. (Nat. Prod. Rep., 2003)

(untitled) - Johnson, W. O.; Kollman, G. E.; Swithenbank, C.; Yih, R. Y. (J. Agric. Food Chem., 1978)

(untitled) - Chan, D. M. T.; Monaco, K. L.; Wang, R.-P.; Winters, M. P. (Tetrahedron Lett., 1998)

(untitled) - Jung, M. E.; Jachiet, D.; Khan, S. I.; Kim, C. (Tetrahedron Lett., 1995)

(untitled) - Burgos, C. H.; Barder, T. E.; Huang, X.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2006)

(untitled) - Kulagowski, J. J.; Rees, C. W. (Synthesis, 1980)

(untitled) - Sawyer, J. S.; Schmittling, E. A.; Palkowitz, J. A.; Smith, W. J., III (J. Org. Chem., 1998)

(untitled) - Zhao, J. K.; Wang, Y. G. (Chin. Chem. Lett., 2003)

(untitled) - Jung, N.; Bräse, S. (J. Comb. Chem., 2009)

(untitled) - Ueno, M.; Yonemoto, M.; Hashimoto, M.; Wheatley, A. E. H.; Naka, H.; Kondo, Y. (Chem. Commun., 2007)

(untitled) - Lee, J.-K.; Fuchter, M. J.; Williamson, R. M.; Leeke, G. A.; Bush, E. J.; McConvey, I. F.; Saubern, S.; Ryan, J. H.; Holmes, A. B. (Chem. Commun., 2008)

(untitled) - Marafie, J. A.; Moseley, J. D. (Org. Biomol. Chem., 2010)

(untitled) - Moseley, J. D.; Woodman, E. K. (Energy Fuels, 2009)

(untitled) - Moseley, J. D.; Kappe, C. O. (Green Chem., 2011)

(untitled) - Iannelli, M.; Bergamelli, F.; Kormos, C. M.; Paravisi, S.; Leadbeater, N. E. (Org. Process Res. Dev., 2009)

(untitled) - Razzaq, T.; Kappe, C. O. (ChemSusChem, 2008)

(untitled) - Dressen, M. H. C. L.; van de Kruijs, B. H. P.; Meuldijk, J.; Vekemans, J. A. J. M.; Hulshof, L. A. (Org. Process Res. Dev., 2010)

(untitled) - Damm, M.; Glasnov, T.; Kappe, C. O. (Org. Process Res. Dev., 2010)

(untitled) - Wienhöfer, I. C.; Studer, A.; Rahman, M. T.; Fukuyama, T.; Ryu, I. (Org. Lett., 2009)

(untitled) - Wiles, C.; Watts, P. (Chem. Commun., 2011)

(untitled) - Fu, X.; Liu, S.; Ruan, X.; Yang, H. (Sens. Actuators, B, 2006)